2012
DOI: 10.1021/jp210990a
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and Regeneration of Camphor-Driven Marangoni Flow with the Addition of Sodium Dodecyl Sulfate

Abstract: We investigated the Marangoni flow around a camphor disk on water with the addition of sodium dodecyl sulfate (SDS). The flow velocity decreased with an increase in the concentration of SDS in the aqueous phase, and flow was hardly observed around the critical micelle concentration (cmc), because SDS reduced the driving force of Marangoni flow. However, the flow velocity increased with a further increase in the concentration of SDS. Thus, the Marangoni flow is maximally inhibited around the cmc of SDS. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…The Marangoni propulsion is caused by an inhomogeneous surface tension around a floating object, often induced by surfactant release from the object [14] or inhomogeneous heating on the object [15,16]. This inhomogeneous surface tension drives surrounding fluid away from the object if the surface tension is lowered around the object, which leads to a characteristic convection flow [14]. The object is then propelled by this flow if the symmetry of the flow field is broken spontaneously [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Marangoni propulsion is caused by an inhomogeneous surface tension around a floating object, often induced by surfactant release from the object [14] or inhomogeneous heating on the object [15,16]. This inhomogeneous surface tension drives surrounding fluid away from the object if the surface tension is lowered around the object, which leads to a characteristic convection flow [14]. The object is then propelled by this flow if the symmetry of the flow field is broken spontaneously [17].…”
Section: Introductionmentioning
confidence: 99%
“…From experiments, it has been found that the surface tension is a decreasing function of the surface concentration of the camphor molecules [24], and we assume a linear relation between γ and u for simplicity:…”
mentioning
confidence: 99%
“…The surface tension γ is assumed to be a decreasing function of u. Based on the experimental measurements [29], we apply the Hill-type function as follows:…”
Section: Mathematical Modelmentioning
confidence: 99%